1999
DOI: 10.1073/pnas.96.17.9821
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive quantitation of cytosine deaminase transgene expression in human tumor xenografts with in vivo magnetic resonance spectroscopy

Abstract: Analysis of transgene expression in vivo currently requires destructive and invasive molecular assays of tissue specimens. Noninvasive methodology for assessing the location, magnitude, and duration of transgene expression in vivo will facilitate subject-by-subject correlation of therapeutic outcomes with transgene expression and will be useful in vector development. Cytosine deaminase (CD) is a microbial gene undergoing clinical trials in gene-directed enzyme prodrug gene therapy. We hypothesized that in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(102 citation statements)
references
References 39 publications
0
102
0
Order By: Relevance
“…Furthermore, studies evaluating 5FC bioavailability and half-life in serum and tissue highlighted a multiple-dose daily regimen. [31][32][33] Although increasing the administration frequency raises concerns about toxicity, 5FC has been used experimentally as an antifungal agent at doses up to 200 mg kg À1 every 6 h for 7 days without signs of toxicity. 35 The current regimen of 500 mg kg À1 four times a day for 4 days did not reveal any signs of toxicity, and permitted a correlation between maximal 5FC bioavailability and high level expression of CD::UPRT at the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies evaluating 5FC bioavailability and half-life in serum and tissue highlighted a multiple-dose daily regimen. [31][32][33] Although increasing the administration frequency raises concerns about toxicity, 5FC has been used experimentally as an antifungal agent at doses up to 200 mg kg À1 every 6 h for 7 days without signs of toxicity. 35 The current regimen of 500 mg kg À1 four times a day for 4 days did not reveal any signs of toxicity, and permitted a correlation between maximal 5FC bioavailability and high level expression of CD::UPRT at the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Meanwhile, other studies demonstrated that the half-life of 5FC was B40 min and that 5FC freely diffused into tissue, [31][32][33] suggesting that after 160 min (that is, four halflives), only 6% of the initial 5FC dose would be present at the tumor. Therefore, an adapted treatment regimen was designed to maximize the bioavailability of CD::UPRT enzyme at the tumor (Figure 5a).…”
Section: Adapting the Prodrug Strategy To Vsv-md51 In Vivomentioning
confidence: 99%
“…8,9 Magnetic resonance spectroscopy has been used to detect gene transfer using cytosine deaminase, arginine kinase, and the murine creatine kinase as reporter genes. [10][11][12] These studies observed the changes in chemical shift of the 19 F or the 31 P isotopes. However, these magnetic strategies have limited temporal resolution and sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…MRS has been used for quantitative noninvasive imaging of tumors. 46 Animals bearing tumors expressing the cDNA encoding for cytosine deaminase from yeast (yCD) were treated with nontoxic 5-fluorocytosine (5-FC) prodrug. The yCDcatalyzed conversion of 5-FC to the chemotherapeutic agent 5-fluorouracil (5-FU) was quantitated in vivo using 19 F MRS.…”
Section: Mri and Mrsmentioning
confidence: 99%